Analysis of COVID-19 in the labor market: “Socioeconomic factors influencing youth unemployment in the district of Sullana, 2020” - Siancas Escobar, Darwin Alejandro (2025)
The objective of this research was to analyze the socioeconomic factors and their influence on youth unemployment in the district of Sullana, using the neoclassical and Keynesian theoretical frameworks. The methodology employed was explanatory, with a non-experimental, cross-sectional design. Data was collected through surveys conducted with 380 residents of the district of Sullana, aged between 18 and 29 years. The Probit model estimation technique was used, and the variables age, gender, student status, head of household status, and work experience were found to be statistically significant. The findings also showed that if an individual gets older and is not currently studying, the probability of being unemployed decreases by 2.59 and 12.18 percentage points, respectively. On the other hand, men are 10.04 percentage points less likely to be unemployed compared to women. Finally, if the individual is not the head of the household and lacks work experience, the probability of being unemployed increases by 20.95 and 17.55 percentage points, respectively.